ANTIFEEDANT EFFICACY OF GREEN SYNTHESIZED ZINC OXIDE NANOPARTICLES AGAINST THE LARVAE OF Papilio demoleus L. - L. MAHESH (The Journal of Research ANGRAU, 2023)
Pongamia pinnata aqueous leaf extracts (PALE) and P.pinnata synthesized Zinc Oxide nanoparticles synthesized (Pp-ZnONPs) efficacy as antifeedants against the 4th instar larvae of Citrus butterfly, Papilio demoleus L. was evaluated in this study conducted between July 2022 and November 2022. GC-MS analysis of PALE confirmed several prominent bioactive compounds to be present in the sample. Scanning Electron Microscope (SEM) results of Pp-ZnONPs confirmed the spherical shape of nanoparticles with an average size of 57.18 nm. In the antifeedant bioassay, the no-choice leaf disc method was employed to assess the antifeedant activity (AFA) at different concentrations of PALE and Pp-ZnONPs solutions separately. The leaf area fed by the larvae was measured by the graph sheet method after 24 and 48 hours of the treatment. The AFA of the test compounds gave dose-dependent results. 70.28% and 64.10% of the highest AFA were obtained with 250 ppm of PALE after 24 and 48 hours of treatment, respectively. For the same periods, 84.38% and 73.92% AFA was observed, respectively with Pp-ZnONPs. The findings showed that both PALE and Pp-ZnONPs have the potential to be used as antifeedants against the 4th instar larvae of P. demoleus.